DIVIDEND POLICY AND ITS IMPACT ON SHAREHOLDERS WEALTH: EVIDENCE FROM CHEMICAL OIL, AND GAS SECTOR COMPANIES LISTED IN PAKISTAN STOCK EXCHANGE (PSX) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this study is to examine the relationship between shareholders' wealth and dividend policy. A sample of 25 companies from the Pakistan stock exchange was selected which includes companies from the chemical sector, oil, and gas sector. Shareholders' wealth is measured with the market price of shares. Dividend per share, retained earnings per share, lagged price-earnings ratio, and return on equity were used as independent variables. The based multiple regression model shows that there is a strong relationship between shareholders' wealth and dividend policy. The shareholder's wealth is increase by dividend policy in the case of Pakistan.